2016
DOI: 10.1186/s13059-015-0864-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of androgen receptor mutations that confer anti-androgen resistance identified in circulating cell-free DNA from prostate cancer patients

Abstract: BackgroundThe androgen receptor (AR) is a pivotal drug target for the treatment of prostate cancer, including its lethal castration-resistant (CRPC) form. All current non-steroidal AR antagonists, such as hydroxyflutamide, bicalutamide, and enzalutamide, target the androgen binding site of the receptor, competing with endogenous androgenic steroids. Several AR mutations in this binding site have been associated with poor prognosis and resistance to conventional prostate cancer drugs. In order to develop an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(217 citation statements)
references
References 52 publications
15
199
0
3
Order By: Relevance
“…The other major phenotypic output of common LBD mutations is antagonist-agonist switching (Supplementary Table 1), which likely explains the withdrawal syndrome observed after cessation of firstgeneration antagonists seen in 15-30% of patients (Small et al 2004). T878A confers agonist properties to flutamide and nilutamide, H875Y to nilutamide and W742C/L to bicalutamide (Veldscholte et al 1990, Suzuki et al 1996, Tan et al 1997, Hara et al 2003, Azad et al 2015, O'Neill et al 2015, Lallous et al 2016. Interestingly, O'Neill and coworkers recently demonstrated that T878A inhibited bicalutamide-activated W742L (O'Neill et al 2015) in what may represent the first evidence of antagonism arising from the heterodimerization of distinct AR mutants.…”
Section: Gata2 Oct1mentioning
confidence: 99%
See 4 more Smart Citations
“…The other major phenotypic output of common LBD mutations is antagonist-agonist switching (Supplementary Table 1), which likely explains the withdrawal syndrome observed after cessation of firstgeneration antagonists seen in 15-30% of patients (Small et al 2004). T878A confers agonist properties to flutamide and nilutamide, H875Y to nilutamide and W742C/L to bicalutamide (Veldscholte et al 1990, Suzuki et al 1996, Tan et al 1997, Hara et al 2003, Azad et al 2015, O'Neill et al 2015, Lallous et al 2016. Interestingly, O'Neill and coworkers recently demonstrated that T878A inhibited bicalutamide-activated W742L (O'Neill et al 2015) in what may represent the first evidence of antagonism arising from the heterodimerization of distinct AR mutants.…”
Section: Gata2 Oct1mentioning
confidence: 99%
“…The advent of the omics era, and resultant integrative genomic analyses of metastatic samples, has further highlighted the extent and frequency of AR pathway alterations in CRPC that may contribute to inappropriate activation or reactivation of this pathway (Grasso et al 2012, Beltran et al 2013, Azad et al 2015, Robinson et al 2015, Lallous et al 2016. Although these alterations have been the subject of other recent excellent articles (for example Penning 2014, Joshi et al 2015, Wyatt & Gleave 2015, this review will specifically focus on ADT-resistance mechanisms driven by direct structural changes to the AR and altered interplay between the AR and its coregulators.…”
Section: Mechanisms Of Persistent Ar Signaling Activity In Crpcmentioning
confidence: 99%
See 3 more Smart Citations